Análisis multitemporal de pérdida de bosque de la región amazónica del municipio de Mapiripán en el departamento del Meta entre los años 2015 a 2022 (2023)
This document aims to carry out a multitemporal analysis over a period of time from 2015 to 2022, regarding the loss of forest in the Amazonian area in the municipality of Mapiripán (Meta). The objective is to determine whether the implementation of the STC4360 ruling of 2018, generated by the Supreme Court of Justice, is decisive in the fight against deforestation in this area.